2020
DOI: 10.3889/oamjms.2020.5146
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Psychological Distress among Filipinos during Coronavirus Disease-19 Pandemic Crisis

Abstract: BACKGROUND: During the coronavirus disease 2019 (COVID-19) pandemic, psychological reactions of the population play a critical role in both the spread of the disease and the occurrence of emotional distress and social disorder. AIM: This study aimed to measure the prevalence and severity of psychological distress to evaluate the current mental health burden on society that leads to the provision of a concrete basis for tailoring and implementing relevant mental health intervention policies to efficiently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Nearly a third of the study's respondents reported symptoms of peritraumatic distress during the pandemic lockdown in China. Similar levels of distress were reported in Italian, 73 French, 74 and Filipino studies, 75 Iranian, 76 and Brazilian 77 studies reported moderate to severe distress in over 60% of their participants. While CPDI levels in many of these studies declined when lockdown periods were lifted, meta-analyses of trauma literature have predictively linked severe levels of peritraumatic distress to subsequent psychopathology.…”
Section: Care Of the Professional Voicesupporting
confidence: 74%
“…Nearly a third of the study's respondents reported symptoms of peritraumatic distress during the pandemic lockdown in China. Similar levels of distress were reported in Italian, 73 French, 74 and Filipino studies, 75 Iranian, 76 and Brazilian 77 studies reported moderate to severe distress in over 60% of their participants. While CPDI levels in many of these studies declined when lockdown periods were lifted, meta-analyses of trauma literature have predictively linked severe levels of peritraumatic distress to subsequent psychopathology.…”
Section: Care Of the Professional Voicesupporting
confidence: 74%
“… 1 The COVID-19 epidemic had a gripping impact not only on health workers, 2 , 3 but also over general population. 4 , 5 , 6…”
Section: Introductionmentioning
confidence: 99%
“…Many studies showed the adverse psychological health effects following quarantine which include emotional disturbance, depression, stress, low mood, irritability, insomnia, post-traumatic stress symptoms, anger, and emotional exhaustion. 4 , 5 , 6 , 7 , 8 , 9 , 10 The reported adverse psychological effects following quarantine include post-traumatic stress symptoms, confusion, anger, stress due to longer quarantine duration, fear of contracting the virus, frustration, boredom, inadequate supplies, inadequate information, financial loss, and stigma. 11 Ethnic group differences, to some extent, have contributed to the level of psychological distress.…”
Section: Introductionmentioning
confidence: 99%